No. IX: IX Symphonie - Kolb, Alois, 1875-1942 (artist):::Creator:::::::::::: (Karl König; Austria; Vienna, 2021)
Engraving depicting the Ninth Symphony, op. 125, with ghostly figures of a man and woman ascending to heaven, and a crowd of human figures on earth with arms outstretched. No. IX from Kolb's cycle of ten engravings.